2015
DOI: 10.25100/cm.v46i1.1654
|View full text |Cite
|
Sign up to set email alerts
|

Práctica basada en la evidencia: creencias, actitudes, conocimientos y habilidades entre fisioterapeutas colombianos

Abstract: Objective: The main purpose of this study was to describe a group of Colombian physical therapists' beliefs and attitudes towards Evidence-Based Practice (EBP), their education, knowledge and skills for implementing EBP, the use of relevant literature in clinical practice, access to and availability of scientific information and perceived barriers to including EBP in practice.Methods: This was a cross-sectional study which involved 1,064 Colombian physical therapists. The study used a 50-item screening questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
50
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(64 citation statements)
references
References 17 publications
11
50
2
1
Order By: Relevance
“…Our findings support the proposal of Snöljung and Gustafsson [40], who note that the barriers encountered by PTs in their implementation of EBP may be related to a lack of expertise and a limited understanding of scientific research. Further, in accordance with our findings, previous studies have also shown that most PTs are interested in improving their EBP skills and that they have a positive attitude towards EBP [41,42].…”
Section: Discussionsupporting
confidence: 93%
“…Our findings support the proposal of Snöljung and Gustafsson [40], who note that the barriers encountered by PTs in their implementation of EBP may be related to a lack of expertise and a limited understanding of scientific research. Further, in accordance with our findings, previous studies have also shown that most PTs are interested in improving their EBP skills and that they have a positive attitude towards EBP [41,42].…”
Section: Discussionsupporting
confidence: 93%
“…Although reliable national data regarding the profile of Colombian PTs is currently lacking, it can be considered that our sample was fairly representative of most practitioners as has been previously described among physical therapists [ 9 22 ]. This study has provided a clear rationale for the further development of methods for identifying barriers among Colombian PTs.…”
Section: Discussionmentioning
confidence: 99%
“…In Latin-American, these discrepancies may be explained by differences in level of academic preparation and access to educational initiatives (e.g. not all professionals have access to a professional development programme) [ 11 , 12 , 21 , 22 ]. Lastly, although Colombian PTs may believe EBP is important, they may not feel it istheir responsibility to undertake all its steps.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main purpose of the study was to screen about EBP in physiotherapy in Ecuador in the public health‐care service. Based on the null evidence available on the topic locally, researches considered the study as the first of this kind being carried out in the country, not so in other countries and regions with similar contexts as the case of Colombia, where Ramírez‐Vélez et al () concluded that physiotherapy professionals expressed a positive attitude about EBP coinciding with most of the controversial results found through this study, where basically in all questions, subjects expressed knowledge, interest, and motivation in relation to EBP in physiotherapy.…”
Section: Discussionmentioning
confidence: 80%